Near-tendon single-fiber electromyography in patients with myopathy - Sirin, Nermin Gorkem; Mehdikhanova, Lala; Bekdik Sirinocak, Pinar; Arkali, Nuran Burcu; Baslo, Mehmet Baris; Kocasoy Orhan, Elif (Neurophysiologie clinique, 2022)
We investigated how properties of single-fiber action potentials (SFAP) and jitter changed in different recording sites in patients with myopathy and controls. SFAP and jitter were recorded using a disposable single-fiber electrode in the biceps brachii muscle of three patients and controls in two sites: i) near the end-plate zone (EPZ), ii) near the tendon. SFAP and spike duration were longer in patients than in controls. Moving the needle away from the EPZ did not change the electrophysiologic parameters. Longer SFAP duration may reflect slow velocity in muscle fibers and serve as an indicator for small fiber size in myopathy.